Prognostic significance of p53, Sox11, and Pax5 co-expression in mantle cell lymphoma - Caixia Jing (Nature Portfolio, 2021)
Abstract Mantle cell lymphoma (MCL) is a relatively rare subtype of non-Hodgkin’s lymphoma. To identify molecular biomarkers in MCL, we performed immunohistochemistry tissue arrays using biopsies from 64 MCL patients diagnosed in West China Hospital from 2012 to 2016. TP53 mutation status in those patients was also examined by sequencing. The sequencing results showed TP53 mutations were highly heterogeneous in MCL. We identified four novel TP53 mutations in MCL: P151R, G199R, V218E, and G325R. The MCL patients with TP53 mutations had inferior progression-free survival (PFS, p = 0.002) and overall survival (OS, p = 0.011). Tissue array results showed the expression of p53, Sox11, or Pax5 alone did not correlate with the patient PFS and OS. However, the MCL patients with triple-positive expression of p53/Sox11/Pax5 had inferior PFS (p = 0.008) and OS (p = 0.002). Such risk stratification was independent to the mantle cell lymphoma international prognostic index (MIPI), Ki-67 value, and TP53 mutation status of the patients. The triple-positive patients might represent a subtype of high-risk MCL. Our findings might indicate a novel way to stratify MCL and predict patients’ prognosis.